Population dynamic of skipjack (Katsuwonus pelamis) in Timor Sea, East Nusa Tenggara, Indonesia. Issue 1 (November 2021) - Herwaty, S; Mallawa, A; Najamuddin,; Zainuddin, M
Abstract: Skipjack tuna is one of the potential fishery commodities in the waters of Timor, East Nusa Tenggara. This fish is exploited throughout the year without any management policies. This study aims to analyse population dynamic parameter. Length data were collected at the Oeba Fish Base from April to December 2020. Data analysis, size structure and age group of the Bhattacharya method, the L∞ and K values of the Ford and Walford method, total mortality by length catch converted curve, natural mortality by Pauly method, Y/R using the Beverton and Holt method. The results showed that the smallest fish was 27 cm FL, the largest was 71 cm FL, the dominant size is 55-58 cm FL and the average length was 48, 68 ± 10, 67 cm FL, L∞ 91.00 cm FL, and K 0.51 year 1 . The population consists of three age groups, the values of Z, M, F and E are 2.64 year 1, 0.86 year 1, 1.78 year 1, and 0.68 year 1 respectively. Current Y/R and optimal Y/R values are 0.036 and 0.060 grams recruit 1 respectively. The conclusion, the high mortality of skipjack tuna is caused by fishing activities, and the high level of exploitation causes the recruitment process to be not optimal.